NORMALISASI SUNGAI BLORONG GUNA MENANGGULANGI BANJIR DI KABUPATEN KENDAL - Dwiyono Abdul Karim; Robi Arsadani (Jurnal Teknik Indonesia, 2022)
Management of water resources in river areas includes 5 aspects, namely conservation of water resources, utilization of water resources, and control of water damage, supported by water resources information systems and community empowerment. The Blorong River area is the area of authority of the PSDA of Central Java Province which is in the administrative area of Kendal Regency. This river often overflows, causing losses to the surrounding area.This research was conducted to analyze the flood inundation caused by the overflow of the Blorong river using the design flood hydrograph used in this study is the Nakayasu synthetic unit hydrograph. Hydraulics analysis using the HEC-RAS 4.1.0 application system (Hydrologic Engineering Center). The cross-sectional data of the river was obtained from PUSDATARU, Central Java Province. The results of the analysis on the Blorong River obtained a high inundation water level profile using the HEC – RAS program.Based on the existing conditions, it is planned to normalize the Blorong River and add embankments to the overflowing river section. The embankment design is an earth embankment with a height of 5.14 calculated from the MAB plus a guard of 0.8 m, the width of the embankment is 3 m. From the calculation results it is known that the embankment is safe against overturning and sliding.Keywords: Blorong River, Flood, River Improvement